Learn Microsoft Power Apps the definitive handbook for building solutions with Power Apps to solve your business needs - Weston, Matthew 1983-; Martín, Elisa Bárcena (Packt, 2023)
The second edition of Learn Microsoft Power Apps will guide you in creating well designed and secure apps that transform old processes and workflows. Learn Microsoft Power Apps starts with an introduction to Power Apps to help you feel comfortable with the creation experience. Using screenshots from the latest UI, you will be guided through how to create an app, building your confidence to start developing further. This book will help you design, set up, and configure your first application by writing simple formulas. You'll learn about the different types of apps you can build in Power Apps and which one applies best to your requirements.
Includes bibliographical references and index
Keywords: COMPUTERS / Business & Productivity Software / Business Intelligence; COMPUTERS / Software Development & Engineering / Systems Analysis & Design; COMPUTERS / Internet / Application Development